Da gênese ao Gênesis: Transformações e permanências no território da Vila Industrial Jundiaí, em Anápolis (GO) - Alves Júnior, Osvaldo Lino (2020)
This research embraces the study of the city construction, territory in time and the urban dynamics that involves themes such as changes in use of the soil, obsolescence, oversights, destruction, demolitions, real estate speculation and new developments, among other urban facts that characterize the cities permanencies and transformations. These issues were covered through the urban analysis imagery that we experience today, systematized by visual analysis, from the territory experience lived and built by man and materialized in an urban landscape fragment of a median-size city from the interior of Brazil. The spatial clipping is Vila Industrial Jundiaí, located in Anápolis (GO), whose origins are linked to the emergence of the first planned neighborhood in the city, Bairro Jundiaí, whose project (dated 1943) was idealized referencing the garden cities urban model, and envisaged in its original plan the creation of an attached industrial conglomerate, which would be called Vila Industrial do Bairro Jundiaí, to shelter the city's industries, isolated from the housing nucleus. The occupation to this claimed agroindustrial district took place only in 1958, the year in which the first paved road was opened from the new federal capital, which connected Brasília to Anápolis. Known and recognized for the amount of agroindustrials sheds it has had since its inception and which constituted of an urban complex idea of very strong historical-cultural relevance in the landscape and in the identity of Anápolis, the district is currently undergoing changes that place the debate about its future on alert. In contrast to this image, a large real estate project, named Genesis Office, whose project adopts the generic architectural language of major global centers is under construction in the neighborhood. Based on the future possibilities in progress and the rugosities in the present, this research tries to contribute to the study of the form and content present in the permanencies and transformations of the territory, analyzing urban realities and utopias. As a methodological path, the contributions of the Visual Analysis method were used, which started from the historical analysis since the origin idea of forming the district, developed in the study of the production territory uses, historically produced, resulting in the visible, identified landscapes, cataloged and analyzed here. A place of memory, the Vila Industrial Jundiaí urban landscape also presents itself as a possible place for the Anápolis city future, based on an element that seeks to act as an inducer of Anápolis city transformation, and which was the key to reading of this research, which try to contribute to the debate about on the relationship between the future and the city's memory.